2018
DOI: 10.1016/j.bjm.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of aflatoxigenic Aspergillus spp. in dairy cattle feed in Southern Brazil

Abstract: The presence of mycotoxins or related fungi in animal feed is a major problem for animal and human health. Silage and concentrated feed samples were collected from 21 dairy farms in the Western part of Paraná state in Southern Brazil. Water activity and pH of all samples were measured, and each sample was analyzed to check for the presence of aflatoxigenic Aspergillus. Water activity was observed to be lower in the concentrated feed samples. The pH was lower in the silage samples, indicating fermentation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
5
0
3
Order By: Relevance
“…It is possible that this occurrence correlates with the reduced amount of water in the dried peanut-based products, which reduces the levels of viable aflatoxigenic fungi. Those results and correlations agree with the results obtained by Variane et al (2018) in corn silage, which is a more humid substrate, where they have obtained A. parasiticus isolates.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that this occurrence correlates with the reduced amount of water in the dried peanut-based products, which reduces the levels of viable aflatoxigenic fungi. Those results and correlations agree with the results obtained by Variane et al (2018) in corn silage, which is a more humid substrate, where they have obtained A. parasiticus isolates.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the authors also found AFB 1 in 37.5% of the fresh fodder and in 41.7% of the corn silage samples with average AFB 1 concentrations of 9.5 and 8.4 µg/kg, respectively, meanwhile AFB 2 was present in only two samples (1.2 and 1.3 µg/kg), and none of the analyzed samples was contaminated by AFG 1 or AFG 2 (Sultana et al, 2017). In Southern Brazil, aflatoxigenic A. parasiticus and A. nomius strains have been detected in the tested silage and concentrated feed samples (Variane et al, 2018).…”
Section: Fungal Activity and Aflatoxin Production In Silagementioning
confidence: 90%
“…It has been reported that ingredients used in animal feed formulations can be contaminated by molds that are capable of producing aflatoxins ( Gelven, 2010 ). This has led to extensive research in order to understand the diversity of Aspergillus species in feeds and feedstuffs ( Variane et al, 2018 ). Findings from previous studies have indicated the presence of a wide range of Aspergillus species in feeds and feedstuffs.…”
Section: Discussionmentioning
confidence: 99%